2001
DOI: 10.1152/ajpcell.2001.280.3.c621
|View full text |Cite
|
Sign up to set email alerts
|

Contractile activity-induced oxidative stress: cellular origin and adaptive responses

Abstract: Previous studies have reported that oxidizing free radical species are generated during exercise, and there has been considerable interest in the potential effects of these on exercising tissues. We hypothesized that contracting skeletal muscle was a major source of oxidizing free radical species and that untrained skeletal muscle would adapt to the oxidative stress of a single short period of contractile activity by upregulation of the activity of cytoprotective proteins in the absence of overt cellular damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
290
2
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(321 citation statements)
references
References 41 publications
15
290
2
14
Order By: Relevance
“…More specifically, during the tissue ischemia, the ATP is degraded to adenosine diphosphate (ADP) and monophosphate (AMP), due to high demand of energy by the muscular tissue. Once the oxygen availability (O 2 ) during the schemic process is reduced, the AMP is continually degraded to hypoxanthine, which is converted in xantine and, later to uric acid by the xantine oxidase enzyme, together with the reduction of the O 2 , producing superoxide radical (•O 2 -) and hydrogen peroxide (H 2 O 2 ) (32) . The moment the tissue is reperfunded, that is, during muscular relaxation, the 2+ , it used the O 2 , which accepts electrons and becomes steady.…”
Section: Lesões àS Fibras Muscularesmentioning
confidence: 99%
“…More specifically, during the tissue ischemia, the ATP is degraded to adenosine diphosphate (ADP) and monophosphate (AMP), due to high demand of energy by the muscular tissue. Once the oxygen availability (O 2 ) during the schemic process is reduced, the AMP is continually degraded to hypoxanthine, which is converted in xantine and, later to uric acid by the xantine oxidase enzyme, together with the reduction of the O 2 , producing superoxide radical (•O 2 -) and hydrogen peroxide (H 2 O 2 ) (32) . The moment the tissue is reperfunded, that is, during muscular relaxation, the 2+ , it used the O 2 , which accepts electrons and becomes steady.…”
Section: Lesões àS Fibras Muscularesmentioning
confidence: 99%
“…The first evidence that exercise induced increases in RONS came from electron spin resonance data [20,48]. Further studies demonstrated that active skeletal muscles released nitric oxide [7], hydroxyl radicals [84], superoxide anions [70] and hydrogen peroxide [71], but only recently it was incontrovertibly demonstrated that mitochondria are the major biological source of ROS production during physical exercise [93]. In fact, there are a number of possible intracellular sources for ROS beside mitochondria, including cytochrome P450, myeloperoxidase, xanthine oxidase, NADH oxidase and peroxisomal oxidative enzymes, all of which may be substantially increased upon exercise.…”
Section: Exercise and Generation Of Reactive Oxygen Andmentioning
confidence: 99%
“…However, exerciseassociated ROS production in the skeletal muscles may be quantitatively limited or, rather, counteracted by anti-oxidants, so that an "unbalance between oxidants and antioxidants in favor of the oxidants", that is oxidative stress, does not necessarily become established. In fact, it was also shown that skeletal muscle adapted to the exercise-induced oxidative environment by upregulating a number of antioxidant enzymes and molecular chaperones [70,71], that allowed it to be protected against a damaging contraction protocol in vitro [72]. In particular, by using a protocol of muscle stimulation in vivo, a rapid transient reduction in muscle protein thiol content, followed by increases in the activities of superoxide dismutase and catalase and in the content of HSP60, HSP70 and haemoxygenase proteins in both EDL and soleus was found [70][71][72].…”
Section: Exercise and Generation Of Reactive Oxygen Andmentioning
confidence: 99%
“…Such adaptive responses occur owing to increased expression or activation of peroxisome proliferator-activated receptor g (PPAR-g) coactivator-1a (PGC-1a) through Ca 21 -dependent pathways, AMP-activated protein kinase (AMPK), and p38 mitogen-activated protein kinases (MAPK) (11,12). However, aside from these positive adaptive responses, oxidative stress due to reactive oxygen species (ROS) also increases within skeletal muscles during muscle contractions (13)(14)(15). Increased oxidative stress, or increased ROS, is known to play a harmful role in the human body, but recent studies have reported its positive effects, such as being involved in mitochondrial biogenesis (13,(16)(17)(18) as well.…”
mentioning
confidence: 99%